2018
DOI: 10.1186/s13717-018-0123-y
|View full text |Cite
|
Sign up to set email alerts
|

Growth and competition among understory plants varies with reclamation soil and fertilization

Abstract: Introduction: Following oil sands mining in Alberta, Canada, the main land management goal is to establish a functioning boreal forest ecosystem, including the understory plant community. One of the challenges with restoring the understory is the presence of non-native species that compete with desirable native species for resources. In a greenhouse experiment, we studied the growth of two native understory species (Galium boreale and Vicia americana) and a non-native invasive species (Matricaria perforata) gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Each species responded differently to the longitudinal and transverse diameters in foliar nutrition applications. This may be based on the availability of the most limiting nutrient for plant development and its efficiency in nutrient utilisation (Buss et al 2018) (Figure 2). The largest P. peruviana fruit achieved using combined nutrients was 16.89 × 16.32 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Each species responded differently to the longitudinal and transverse diameters in foliar nutrition applications. This may be based on the availability of the most limiting nutrient for plant development and its efficiency in nutrient utilisation (Buss et al 2018) (Figure 2). The largest P. peruviana fruit achieved using combined nutrients was 16.89 × 16.32 mm.…”
Section: Resultsmentioning
confidence: 99%
“…However, competition will likely play a larger role in structuring the vegetation community in the future once all available growing space is occupied. The initial spike of non-native species on FFMM indicates a combination of species exploiting initial resources (Alday et al 2011;Buss et al 2018;Gingras-Hill et al 2018) and the higher amounts of seeds present within the seedbank in the FFMM (Errington and Pinno 2015;Mackenzie and Naeth 2010). Over time on the FFMM the species cover remained relatively constant but continued to increase on PMM, this is related to the available growing space (bare soil).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hansen and Daniel (1985) reported that a lack of weed control practices can result in 50% or more reduction in crop production. Also, Buss et al (2018) suggested that we need to be cautious practically when the fertilizer is applied to reclamation lands because it may induce an unexpected result of high production for undesirable plants with the loss of desirable crop trees. As the initial weed growth in this study was vigorous and well-established before the crop trees were planted, they could take up the soil nutrients better than the crop trees.…”
Section: Discussionmentioning
confidence: 99%